Epstein-Barr virus and skin - Martin Sangueza-Acosta; Erica Sandoval-Romero (Sociedade Brasileira de Dermatologia, 2018)
Abstract: Epstein-Barr virus is a DNA virus infecting human beings and could affect 90% of human population. It is crucial to take in account that in Latin America, unlike what happens in developed countries, the exposure to the virus is very early and therefore people have a much longer interaction with the virus. The virus is related to many diseases, mainly the oncological ones, and when the onset is in cutaneous tissue, it can present many clinical variants, as well acute as chronic ones. Among the acute ones are infectious mononucleosis rash and Lipschutz ulcers; the chronic presentations are hypersensivity to mosquito bites, hydroa vacciniforme, hydroa vacciniforme-like lymphoma, its atypical variants and finally nasal and extra-nasal NK/T-cell lymphoma. Although they are not frequent conditions, it is crucial for the dermatologist to know them in order to achieve a correct diagnosis.